Photosynthetic Production of Ulva rotundata Bliding Estimated by Oxygen and Inorganic Carbon Exchange Measurements in the Field - Mercado, Jesús; Avilés-Benítez, Antonio; Benítez, Ernesto; Carrasco, María; Palomo, Laura; Clavero, Vicente; Niell-Castanera, Francisco Javier (Gruyter, 2003)
The photosynthetic performance of an estuarine population of. Ulva rotundata Bliding was determined under natural radiation during a daily cycle. The primary production was estimated fol1owing two methods, oxygen evolution and dissolved inorganic carbon (DIC) uptake calculated from the pH change and alkalinity in the media after incubation in closed bottles. Maximum values of oxygen evolution (261 µmol O2 m-2 min-1) were reached during midday. The daily course of the DIC uptake rates was different since the maximum rate (248±10 µmol C m-2 min-1) was obtained later in the afternoon. In any case, no photoinhibition was detected by either O2 evolution or DIC uptake. Additionally, the parameters of photosynthesis vs. photon fluence density curves were similar in spite of the technique used. During the daily cycle, significant changes in CA activity and percentage of photosynthetic inhibition following the addition of an external CA inhibitor (acetazolamide) were produced. However, these changes appeared to have a limited effect on photosynthesis. On the other hand, chlorophyll a and b contents decreased drastically in the afternoon and there was not a good correlation between pigment content and photosynthesis rates. Taken into account the results obtained, the daily primary production of U. rotundata based on oxygen evolution was 20% higher than-that based on DIC up take (1.8 and 1.5 g C m-2 day-1, respedively).
Keywords: Fotosíntesis; Carbonic anhydrase; photoinhibition; photosynthetic quotient; photosynthesis; Ulva